ORGANISATIONAL CLIMATE CHARACTERISTICS OF PROSPECTIVE OFFICERS' INITIAL TRAINING ORGANISATION CONCLUSIONS OF A RESEARCH STUDY - CRISTINA PIELMUŞ (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. This study presents the conclusions of a broader research initiative carried out over a period of three years, between 2008 and 2011. The larger research study focused on making an interpretive analysis of the organisational culture as a determinant of school climate with a view to identify those factors that affect the teaching staff's degree of satisfaction and the students' level of academic achievement in the organizations for the initial training of prospective police officers. The research stage, which is the object of the present study, aims at identifying those features that characterize the climate of the educational organisations in charge of the initial training of prospective officers. Moreover, the study attempts to demonstrate the climate's potential influence on the teachers' job satisfaction and the students' academic performance.